(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
Abstract The aim of this study is to see the effect of adding different levels Saccharomyces cerevisiae to the feed or the drinking water on the characteristics of eggs production and the qualitative characteristics of the local quail eggs. The levels (0, 1, 1.5, 2 and 2.5%) of yeast to the feed and 0.5 g / L in the drinking water for 324 birds as a total number. The birds were randomly distributed into six treatments; each of which included 54 bird/treatment and with 6 replicates (9 birds/replicate). The statistical analysis results showing A significant improvement showed that there was an improvement in the daily production rate of eggs (%H.D.P.), the mass of the egg (g/female bird/week) and the number of the eggs for the treatments characterized with high levels of Saccharomyces cerevisiae in the feed (2 and 2.5% of Saccharomyces cerevisiae in the feed). On the contrary, there was no significant effect on the weight of the average fodder consumed for the treatments that include Saccharomyces cerevisiae compared with the control treatment. Feed conversion ratio rate was improved in the third treatment and was higher compared with the rest of the treatments as its value was (3.17). Yet, there were no significant differences among the rest of the treatment and the control treatment in terms of the coefficient of feed conversion ratio. Moreover, it was observed that there was a significant improvement in the weight of the egg shell and its thickness in favor of the Saccharomyces cerevisiae addition treatments compared with the control treatment. As for the characteristics of the index of yolk, white, hue unit and the shape of the egg, the differences were not significant compared with the control treatment.